MicroLingo: Chatbot WhatsApp Berbasis AI untuk Pelatihan Bahasa Inggris dengan Pendekatan Microlearning untuk Pelaku UMKM Generasi Z di Indonesia - Syekh Maulana Wijaya; Maria El Qibthiya Az Zahra; Prawita, Fat'hah Noor (Universitas Telkom, 2025)
MicroLingo: AI-based WhatsApp Chatbot to Practice English with a Microlearning Approach for Generation Z SME Actors in Indonesia. In the era of industry 4.0, proficiency in English is crucial, especially for SME actors who form the backbone of Indonesia’s economy. MicroLingo is an AI-based English language training platform implemented as a WhatsApp chatbot using microlearning approach. This platform is designed to help Generation Z SME actors improve their English skills in an accessible and understandable manner. This final project aims to address the limitations of similar previous applications, such as Duolingo, by adding pitching simulation feature and using the microlearning method. MicroLingo leverages various technologies such as LangChain with OpenAI to provide LLM with augmented data from MicroLingo materials, and the WhatsApp API for integration with the WhatsApp application. The outcome of this project is expected to expand user coverage by providing interactive and flexible English training. By using the microlearning approach, each learning module is broken down into small units that can be completed in a short time. This allows users to practice English in their spare time with more focus and flexibility. The use of WhatsApp as the main platform also minimizes hardware requirements, making MicroLingo accessible to more users. Although the primary target is young SME actors in Indonesia, MicroLingo is designed to be used by anyone who wants to learn English easily, anytime and anywhere.